Prevalence of hepatitis delta virus (HDV) infection in chronic hepatitis B patients in eastern Turkey: still a serious problem to consider - Bahcecioglu, I. H.; Aygun, C.; Gozel, N.; Poyrazoglu, O. K.; Bulut, Y.; Yalniz, M. (Wiley, 2011)
Hepatitis delta virus (HDV) is a serious cause of liver-related morbidity and mortality. Coexistent infection with HDV tends to aggravate the course of hepatitis B virus (HBV)-associated liver disease. The aim of this study was to determine the prevalence of HDV infection among patients chronically infected with HBV in the Elazig region, which is in eastern Turkey. A group of 282 patients infected with chronic HBV were investigated for the study. Anti-HDV seropositivity was evaluated in all patients. The anti-HDV-positive patients were further tested for HDV RNA. Severity of liver disease was assessed by liver biopsy. Regression analysis was used to determine the relationship between independent variables and HDV positivity. Of 282 chronic HBV patients, 192 were men (68.1%) and 90 were women (31.9%). The mean age was 43.8 +/- 12.7 (between 18 and 73 years). Anti-HDV was positive in 45.5% of the patients (128/282). Among the 128 anti-HDV-positive patients, 116 were checked for HDV RNA and 56.9% were found positive (66/116). Chronic HDV infection rate was therefore present in at least 23.4% of the whole study group (66/282). There were 83 patients with cirrhosis (29.4%) in the study group. Anti-HDV seroprevalence and HDV RNA presence were higher in those with cirrhosis (61.4% and 42.2%, respectively). No significant relationship was found between anti-HDV seropositivity and demographic factors such as age, sex and operation or transfusion history except family history. HDV-RNA-positive patients had significantly higher ALT and lower albumin levels when compared to HDV-RNA-negative patients. HDV-RNA-positive patients also had a significantly higher fibrosis stage. In conclusion, these findings demonstrated that HDV infection is endemic and still a serious problem in the Elazig region of eastern Turkey. HDV infection is significantly related to the family exposure and increases the risk of severe liver fibrosis in this region.
Keywords: chronic hepatitis B; cirrhosis; hepatitis delta virus